Effects of online exercise intervention on physical and mental conditions in young adults with chronic neck pain - Yiting Lin; Raymond Tsang; Jinzhuo Hu; Ning Zhao; Xinyu Zhu; Jiangshan Li; Jinghua Qian (iScience, 2023)
Summary: This study aimed to compare the efficacy of online exercise therapy with conventional exercise therapy for young adults with chronic neck pain. A randomized clinical trial recruiting 35 university students with self-reported chronic neck pain was conducted. The experimental group receiving 6-week online exercise therapy and active control group receiving the same face-to-face conventional exercise therapy. Visual analogue scale (VAS) for pain, Neck Disability Index (NDI), Work Limitations Questionnaire (WLQ), Hospital Anxiety and Depression Scale (HADS) and its subscales were evaluated. Both groups had improvements in VAS, NDI, HADS and WLQ scores from baseline to 6 weeks. All comparisons of changes in outcome variables between groups were not statistically significant. For young adults with chronic neck pain, both the online and conventional exercise interventions could improve their pain level, neck disability, anxiety state, and work efficiency. The online exercise intervention appeared feasible as an alternative treatment option for them.